Implementasi Sistem Pakar Diagnosis Penyakit Hemoroid (WASIR) dengan Metode Dempster-Shafer - Andref Lamsinar (UNIVED Press, 2025)
Hemorrhoids are a condition characterized by the inflammation and dilation of the venous blood vessels around the anus, originating from the hemorrhoidal plexus. This condition is usually experienced by elderly individuals aged 35-45 years. However, due to changing lifestyle patterns, many younger individuals are also affected. Several factors contribute to the development of hemorrhoids, such as prolonged motorcycle or bicycle riding, unhealthy eating habits, insufficient water intake, and lack of exercise. Diagnosing hemorrhoids is often challenging due to the social stigma that makes patients reluctant to consult a doctor. Therefore, an artificial intelligence system is needed to assist in diagnosing hemorrhoid disease, drawing from the expertise of medical and health professionals to facilitate the diagnosis process. One area of artificial intelligence is expert systems, which combine the reasoning abilities of an expert and adopt expert knowledge into a computer system designed to represent the problem-solving capabilities of a human expert. By implementing the Dempster-Shafer method in this expert system, the goal is to diagnose hemorrhoid disease based on the symptoms experienced by patients through a web-based platform. The implementation of this expert system is expected to reduce the workload of medical personnel and improve the quality of life for patients by providing quick and accurate diagnoses.